Social Accountability and Public Voice through Community Radio Programming - World Bank (Washington, DC, 2012)
Empowerment of the poor and social accountability have become core values of decentralization and democratization processes around the world, and are key to effective poverty reduction. Access to information and means to report and comment on issues of local interest are recognized as critical enablers for empowerment and social accountability. Mechanisms that promote accountability on the part of public institutions (supply side in terms of horizontal accountability) as well as mechanisms that promote governments being held accountable by civil society (demand side in terms of social and vertical accountability) are both essential for achieving effective sustainable development outcomes. Most communications initiatives supported by the World Bank and other donors have focused primarily on the supply side of accountability and not on strengthening the demand side through actions that enable the poor and civil society organizations (CSOs) to create and effectively utilize spaces for public voice and community mobilization. The poor have limited influence in the production of information and limited access to channels of communication in most countries borrowing from the World Bank. This condition is reflected in two areas: the concentration on ownership of key media institutions and asymmetric access to mediums of communication.